Wound repair film as well as preparation method and application thereof
Through the cross-linking reaction of sodium hyaluronate and sulfonated chitosan with curcumin and arginine, wound repair membranes with antibacterial, antioxidant and pro-angiogenesis were prepared, which solved the problem of difficulty in healing in diabetic wounds and achieved Efficient wound healing effect.
Patent Information
- Application Number
- CN202411443420.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-01-03
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Diabetic wounds are difficult to heal due to high sugar environment and risk of bacterial infection. Existing dressings cannot provide effective wetting, antibacterial, anti-inflammatory and pro-angiogenic functions, resulting in the healing process being blocked.
The sponge-like membrane dressing is prepared by cross-linking reactions of sodium hyaluronate, curcumin, arginine and zinc ions or sodium hyaluronate, sulfonated chitosan, curcumin, arginine and zinc ions, and the sponge-like membrane dressing is prepared and frozen The drying technology produces a wound repair film, which has multiple effects of isolating bacteria, keeping moisture, antioxidant and promoting healing.
This wound repair membrane can effectively isolate bacteria, keep the wound moist, have antioxidant and hemostasis effects, significantly promote diabetic wound healing, and has low raw materials, simple process, high safety, and strong clinical use value.
Smart Images

Figure CN119236161A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of biomedical materials, and in particular to a wound repair membrane and a preparation method and application thereof. Background Art
[0002] Wounds are divided into acute and chronic wounds. Acute wounds can recover in a short period of time, but the size, depth and degree of damage of the wound affect the healing process. In addition, chronic wounds take a long time to heal and the healing process is different from that of acute wounds. The healing process of acute wounds is normal, timely and orderly. However, the repair of chronic wounds is challenging, and it is often difficult for the wound surface to restore its normal anatomical structure and function. Diabetic wounds are a common chronic wound infection. In a high-sugar environment, diabetic wounds have an extremely high risk of bacterial infection and poor promotion of angiogenesis, which will hinder wound healing.
[0003] Inappropriate dressings will make diabetic wounds difficult to heal and fail to provide a moist environment. Ideal diabetic wound dressings should have good antibacterial, anti-inflammatory, antioxidant, and angiogenesis-promoting properties to ensure effective healing of diabetic wounds, and the economic efficiency of the dressing should also be taken into consideration. Summary of the invention
[0004] In view of this, an embodiment of the present disclosure provides a method for preparing a wound repair membrane, which at least partially solves the problems existing in the prior art.
[0005] In a first aspect, an embodiment of the present disclosure provides a method for preparing a wound repair membrane, the preparation method comprising:
[0006] Step (1): Dissolve sodium hyaluronate in deionized water and add appropriate amount of Zn 2+ , stir evenly to obtain sodium hyaluronate / Zn 2+ Solution;
[0007] Step (2) dissolving curcumin in arginine and uniformly stirring at a set temperature to obtain a curcumin / arginine solution;
[0008] Step (3): The sodium hyaluronate / Zn obtained in step (1) 2+ The solution is added to the curcumin / arginine solution obtained in step (2), and stirred evenly to obtain a sodium hyaluronate-curcumin-arginine-zinc ion mixed solution;
[0009] Step (4): introducing the sodium hyaluronate-curcumin-arginine-zinc ion mixed solution obtained in step (3) into a repair film preparation mold, and freeze-drying under set conditions to obtain a sodium hyaluronate-curcumin-arginine-zinc ion freeze-dried film.
[0010] According to a specific implementation of the embodiment of the present disclosure, step (5): the preparation method further comprises: dissolving sulfonated chitosan in deionized water, adding a certain amount of Zn 2+ , stir evenly to obtain sulfonated chitosan / Zn 2+ Solution;
[0011] The step (3) comprises: mixing the sodium hyaluronate / Zn obtained in step (1) 2+ Solution and the sulfonated chitosan / Zn obtained in step (5) 2+ The solution was mixed according to the set ratio, added to the curcumin / arginine solution, and stirred evenly to obtain sodium hyaluronate / sulfonated chitosan-curcumin / arginine-Zn 2+ Mixing solutions;
[0012] Step (4) comprises: introducing the sodium hyaluronate-curcumin-arginine-zinc ion mixed solution obtained in step (3) into a repair film preparation mold, and freeze-drying under set conditions to obtain sodium hyaluronate / sulfonated chitosan-curcumin / arginine-Zn 2+ Lyophilize the membrane.
[0013] According to a specific implementation of the embodiment of the present disclosure, the mass ratio of curcumin to arginine in step (2) is 1:18; and the set temperature in step (2) is 60-80°C.
[0014] According to a specific implementation of the embodiment of the present disclosure, the mass concentration of sodium hyaluronate in step (1) is 10 mg / mL, and Zn is added 2+ The concentration is 60 μmol / L.
[0015] According to a specific implementation method of the embodiment of the present disclosure, the set conditions for freeze drying under set conditions in the step (4) are: the freeze drying temperature is -60~-70°C, the freeze drying vacuum degree is 1~5Pa, and the freeze drying time is 20~24h.
[0016] According to a specific implementation of the embodiment of the present disclosure, the mass ratio of sodium hyaluronate to sulfonated chitosan in step (3) is 1:0.5, and the sodium hyaluronate / Zn 2+ Solution and sulfonated chitosan / Zn 2+ The mass ratio of the mixed solution to curcumin / arginine was 1:0.4.
[0017] According to a specific implementation method of the embodiment of the present disclosure, the set conditions for freeze drying under set conditions in the step (5) are: the freeze drying temperature is -60~-70°C, the freeze drying vacuum is 1~5Pa, and the freeze drying time is 20~24h.
[0018] On the other hand, an embodiment of the present disclosure provides a wound repair membrane, which is prepared by the wound repair membrane preparation method as described above.
[0019] The present invention provides a wound repair film based on polysaccharide-curcumin-arginine-zinc ion and a preparation method thereof. The present invention divides the polysaccharide-based polymer materials into two systems for research. System 1: a sponge-like film dressing is formed by cross-linking sodium hyaluronate, curcumin, arginine and zinc ions. It is proved by infrared that sodium hyaluronate, curcumin, arginine and zinc ions are successfully cross-linked together to obtain a new hyaluronic acid polysaccharide polymer material. System 2: a sponge-like film dressing is formed by cross-linking sodium hyaluronate, sulfonated chitosan, curcumin, arginine and zinc ions. It is proved by infrared that sodium hyaluronate, sulfonated chitosan, curcumin, arginine and zinc ions are successfully cross-linked together to obtain a new hyaluronic acid / sulfonated chitosan polysaccharide polymer material. The present invention proves through a series of experiments that the polymer material has multiple functions such as isolating bacteria, keeping wounds moist, anti-oxidation, hemostasis and promoting healing of diabetic wounds. In addition, the main raw materials of the preparation method provided by the invention are cheap and easily available, the synthesis conditions are mild, the production route is simple, the process flow is simple, the operability is strong, the process is simple, and the production quality is easier to control. Compared with commercially available products, it has higher safety and clinical use value. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the technical solutions of the embodiments of the present disclosure, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present disclosure. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0021] Figure 1 The morphology of the membrane material of the system, where a is HA, b is HA-Cur / Arg, and c is HA-Cur / Arg-Zn 2+ ;
[0022] Figure 2 The morphology of the two membrane materials in the system, where a is HA / SCS, b is HA / SCS-Cur / Arg, and c is HA / SCS-Cur / Arg-Zn 2+ ;
[0023] Figure 3 Diameter and thickness diagram of membrane materials, where a is the diameter diagram of HA / SCS, b is the thickness diagram of HA / SCS, and c is the diameter diagram of HA-Cur / Arg and HA-Cur / Arg-Zn 2+ , HA / SCS-Cur / Arg, HA / SCS-Cur / Arg-Zn 2+Diameter diagram, d is HA-Cur / Arg, HA-Cur / Arg-Zn 2+ , HA / SCS-Cur / Arg, HA / SCS-Cur / Arg-Zn 2+ Thickness map of
[0024] Figure 4 The infrared spectrum of the membrane material of the system, where a is HA, b is Cur, c is Arg, d is Cur / Arg, e is ZnSO4·7H2O, f is the physical mixture of HA, Cur, Arg and ZnSO4·7H2O, g is HA-Cur / Arg, h is HA-Cur / Arg-Zn 2+ ;
[0025] Figure 5 The infrared spectra of the two membrane materials of the system, where a is HA, b is CS, c is SCS, d is Cur, e is Arg, f is Cur / Arg, g is ZnSO4·7H2O, h is HA / SCS, i is a physical mixture of HA, SCS, Cur, Arg and ZnSO4·7H2O, j is HA / SCS-Cur / Arg, and k is HA / SCS-Cur / Arg-Zn 2+ ;
[0026] Figure 6 DSC spectrum of differential scanning calorimetry analysis of system-membrane material, where a is HA-Cur / Arg-Zn 2+ , b is HA-Cur / Arg, c is a physical mixture of HA, Cur, and Arg, d is ZnSO4·7H2O, e is Cur / Arg, and f is HA;
[0027] Figure 7 DSC spectrum of the differential scanning calorimetry analysis of the two membrane materials of the system, where a is HA / SCS-Cur / Arg-Zn 2+ , b is HA / SCS-Cur / Arg, c is a physical mixture of HA, SCS, Cur, and Arg, d is ZnSO4·7H2O, e is Cur / Arg, f is HA / SCS, g is HA, h is SCS, and i is CS;
[0028] Figure 8 The water vapor permeability diagram of the system membrane material, where a is HA, b is HA-Cur / Arg, and c is HA-Cur / Arg-Zn 2+ ;
[0029] Fig. 9The water vapor permeability diagram of the two membrane materials of the system, where a is HA, b is CS, c is SCS, d is HA / SCS, e is HA / SCS-Cur / Arg, and f is HA / SCS-Cur / Arg-Zn 2+ ;
[0030] Fig.10 It is the antioxidant diagram of the in vitro antioxidant test of the system-membrane material;
[0031] Fig.11 It is the antioxidant graph of the in vitro antioxidant test of the system two membrane materials;
[0032] Fig.12 The results of the in vitro antibacterial test of the membrane material of system 1, where a is HA, b is HA-Cur / Arg, and c is HA-Cur / Arg-Zn 2+ , d is blank;
[0033] Fig.13 The results of in vitro antibacterial test of the membrane materials of system II, where a is CS, b is SCS, c is HA / SCS, d is HA / SCS-Cur / Arg, and e is HA / SCS-Cur / Arg-Zn 2+ ,fblank;
[0034] Fig.14 The results of the in vitro hemolytic test of the membrane material of the system 1, where a is HA, b is HA-Cur / Arg, and c is HA-Cur / Arg-Zn 2+ , d is the positive control;
[0035] Fig.15 The results of the in vitro hemolytic test of the two membrane materials of the system, where a is HA, b is SCS, c is HA / SCS, d is HA / SCS-Cur / Arg, and e is HA / SCS-Cur / Arg-Zn 2+ , f is the positive control;
[0036] Fig.16 The results of the wound healing test of the membrane material of the system, where a is the diabetic blank, b is the normal blank, c is the 3Tegaderm dressing, d is HA, e is HA-Cur / Arg, and f is HA-Cur / Arg-Zn 2+ ;
[0037] Fig.17 The results of the wound healing test of the two membrane materials in the system, where a is the diabetic blank, b is the normal blank, c is the 3Tegaderm dressing, d is HA, e is SCS, f is HA / SCS, g is HA / SCS-Cur / Arg, and h is HA / SCS-Cur / Arg-Zn 2+ .
[0038] Definition: HA-sodium hyaluronate, Cur-curcumin, Arg-arginine, HA-Cur / Arg-sodium hyaluronate-curcumin / arginine, HA-Cur / Arg-Zn 2+ ——Sodium hyaluronate-curcumin / arginine-zinc ion, CS-chitosan, SCS-sulfonated chitosan, HA / SCS——Sodium hyaluronate / sulfonated chitosan. DETAILED DESCRIPTION
[0039] The embodiments of the present disclosure are described in detail below with reference to the accompanying drawings.
[0040] The following describes the embodiments of the present disclosure through specific examples, and those skilled in the art can easily understand other advantages and effects of the present disclosure from the contents disclosed in this specification. Obviously, the described embodiments are only a part of the embodiments of the present disclosure, rather than all of the embodiments. The present disclosure can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present disclosure. It should be noted that the following embodiments and features in the embodiments can be combined with each other without conflict. Based on the embodiments in the present disclosure, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present disclosure.
[0041] It should be noted that various aspects of the embodiments within the scope of the appended claims are described below. It should be apparent that the aspects described herein may be embodied in a wide variety of forms, and any specific structure and / or function described herein is merely illustrative. Based on the present disclosure, it should be understood by those skilled in the art that an aspect described herein may be implemented independently of any other aspect, and two or more of these aspects may be combined in various ways. For example, any number of aspects described herein may be used to implement the device and / or practice the method. In addition, other structures and / or functionalities other than one or more of the aspects described herein may be used to implement this device and / or practice this method.
[0042] It should also be noted that the illustrations provided in the following embodiments are only schematic illustrations of the basic concept of the present disclosure. The drawings only show components related to the present disclosure rather than being drawn according to the number, shape and size of components in actual implementation. In actual implementation, the type, quantity and proportion of each component may be changed arbitrarily, and the component layout may also be more complicated.
[0043] Additionally, in the following description, specific details are provided to facilitate a thorough understanding of the examples. However, it will be understood by those skilled in the art that the aspects described may be practiced without these specific details.
[0044] The disclosed embodiments provide two systems of wound repair membrane preparation methods. In this embodiment, system one and system two are used to distinguish the descriptions of the two preparation methods.
[0045] The preparation method of system 1 is as follows:
[0046] Step (1): Dissolve sodium hyaluronate in deionized water and add appropriate amount of Zn 2+ , stir evenly to obtain sodium hyaluronate / Zn 2+ Solution; Zn added therein 2+ It can be a solution such as ZnSO4;
[0047] Step (2) dissolving curcumin in arginine and uniformly stirring at a set temperature to obtain a curcumin / arginine solution;
[0048] Step (3): The sodium hyaluronate / Zn obtained in step (1) 2+ The solution is added to the curcumin / arginine solution obtained in step (2), and stirred evenly to obtain a sodium hyaluronate-curcumin-arginine-zinc ion mixed solution;
[0049] Step (4): introducing the sodium hyaluronate-curcumin-arginine-zinc ion mixed solution obtained in step (3) into a repair film preparation mold, and freeze-drying under set conditions to obtain a sodium hyaluronate-curcumin-arginine-zinc ion freeze-dried film.
[0050] In the present invention, the mass concentration of the sodium hyaluronate solution is preferably 5 mg / mL to 15 mg / mL, more preferably 10 mg / mL.
[0051] In the present invention, the Zn2+ concentration is preferably 15 mg / mL, more preferably 60 μmol / L.
[0052] In the present invention, the stirring is preferably magnetic stirring at room temperature, the rotation speed of the magnetic stirring is preferably 600 rpm, and the stirring time is preferably 10 h to 14 h.
[0053] In the present invention, arginine is used to dissolve curcumin, preferably the water bath temperature is 70° C., the stirring is magnetic stirring, and the time is 48 hours.
[0054] The preparation method of system 2 is as follows:
[0055] Step (1): Dissolve sodium hyaluronate in deionized water and add a certain amount of Zn 2+ , stir evenly to obtain sodium hyaluronate / Zn 2+ Solution; Zn added therein 2+ It can be a solution such as ZnSO4;
[0056] Step (2): Dissolve sulfonated chitosan in deionized water and add a certain amount of Zn 2+ , stir evenly to obtain sulfonated chitosan / Zn 2+ Solution;
[0057] Step (3): dissolving curcumin in arginine and stirring at a set temperature to obtain a curcumin / arginine solution;
[0058] Step (4): The sodium hyaluronate / Zn obtained in step (1) 2+ Solution and the sulfonated chitosan / Zn obtained in step (2) 2+ The solution was mixed according to the set ratio, added to the curcumin / arginine solution obtained in step (3), and stirred evenly to obtain sodium hyaluronate / sulfonated chitosan-curcumin / arginine-Zn 2+ Mixing solutions;
[0059] Step (5): The sodium hyaluronate-curcumin-arginine-zinc ion mixed solution obtained in step (3) is introduced into the repair film preparation mold, and freeze-dried under set conditions to obtain sodium hyaluronate / sulfonated chitosan-curcumin / arginine-Zn 2+ Lyophilize the membrane.
[0060] The mass concentration of sodium hyaluronate in step (1) is 10 mg / mL, and Zn is added 2+ The concentration is 60 μmol / L.
[0061] The mass ratio of sodium hyaluronate to sulfonated chitosan in step (4) is 1:0.5. 2+ Solution and sulfonated chitosan / Zn 2+ The mass ratio of the mixed solution to curcumin / arginine was 1:0.4.
[0062] The freeze drying conditions under the set conditions in step (5) are: the freeze drying temperature is -60~-70°C, the freeze drying vacuum degree is 1~5Pa, and the freeze drying time is 20~24h.
[0063] In the present invention, the size of the mold for preparing the wound repair membrane is preferably a six-well plate, and the mold is in the sodium hyaluronate / Zn 2+-Cur / Arg mixed solution needs to be disinfected before pouring; the freeze drying temperature is independently -60~-70℃, preferably -62~-68℃, and more preferably -65℃; the freeze drying vacuum is independently 1~5kPa, preferably 2~4Pa, and more preferably 3Pa; the freeze drying time is independently 20~24h, preferably 21~23h, and more preferably 22h. The present invention adopts freeze drying technology, and the obtained film dressing has excellent morphology and loose structure, and is easy to absorb a large amount of exudate from diabetic wounds.
[0064] In the present invention, in the present invention, the mixed solution of system one can combine sodium hyaluronate, curcumin, arginine, and zinc ions together by cross-linking, and the mixed solution of system two can combine sodium hyaluronate, sulfonated chitosan, curcumin, arginine, and zinc ions together by cross-linking. A novel polysaccharide-based polymer material is obtained respectively, and the polymer material has multiple functions such as being able to isolate bacteria, keep the wound surface moist, resist oxidation, stop bleeding, and promote the healing of diabetic wounds. Compared with existing similar products, it has higher safety and clinical use value. In the present invention, the cross-linking state of the hyaluronic acid polysaccharide polymer material is detected by differential scanning calorimetry (DSC); the properties of the obtained polymer material are verified by swelling rate test, in vitro antioxidant test, in vitro antibacterial test, in vitro hemolytic test, and diabetic wound healing test.
[0065] The present invention also provides a wound repair membrane obtained based on the above preparation method, and the obtained wound repair membrane is a polysaccharide-based polymer material.
[0066] The present invention also provides an application of the polysaccharide-based polymer material in preparing a diabetic skin wound healing dressing.
[0067] In the present invention, the obtained polysaccharide-based polymer material is natural and degradable, can absorb a large amount of exudate from diabetic wounds, maintain a moist environment for diabetic wounds, is antibacterial and promotes diabetic wound healing, and will not adhere to diabetic wound tissues. Removal of the polymer material will not cause secondary damage to the surface of the diabetic wound.
[0068] The present invention has no special limitation on the preparation method of the diabetic skin wound healing dressing, and the preparation method of the corresponding dressing can be used. The present invention has no special limitation on the existence form and amount of the polysaccharide polymer material in the diabetic skin wound dressing, and the conventional existence form and amount in the dressing can be used.
[0069] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.
[0070] In the present invention, all reagents in the following embodiments and test examples are commercially available unless otherwise specified, and are chromatographically pure or analytically pure.
[0071] Example 1
[0072] (1) System 1: Take 0.1 g of sodium hyaluronate, dissolve it in 10 mL of deionized water, and stir it magnetically at room temperature for 12 h to obtain a sodium hyaluronate solution;
[0073] System 2: Take 0.1 g of sodium hyaluronate, dissolve it in 10 mL of deionized water, and stir it magnetically at room temperature for 12 h to obtain a sodium hyaluronate solution; take 0.1 g of sulfonated chitosan, dissolve it in 10 mL of deionized water, and stir it magnetically at room temperature for 2 h to obtain a sulfonated chitosan solution;
[0074] (2) System 1: Take 0.1725 mg Zn 2+ , add to the sodium hyaluronate solution in (1), stir evenly, and obtain sodium hyaluronate / Zn 2+ Solution;
[0075] System 2: Take 0.1725 mg Zn 2+ , add it to the sulfonated chitosan solution in (1), stir evenly, and obtain sulfonated chitosan / Zn 2+ Solution;
[0076] (3) Take the sodium hyaluronate / Zn obtained in (2) 2+ The solution and Cur / Arg solution were added into the mold at a mass ratio of 1:0.4 and stirred evenly to obtain sodium hyaluronate / Zn 2+ Curcumin arginine mixed solution; take the sodium hyaluronate / Zn obtained in (2) 2+ Solution and sulfonated chitosan / Zn 2+ The solution was added into the mold at a ratio of 1:0.5 and stirred evenly to obtain sodium hyaluronate / Zn 2+ and sulfonated chitosan / Zn 2+ The mixed solution was then added with Cur / Arg solution at a mass ratio of 1:0.4 and stirred evenly to obtain sodium hyaluronate sulfonated chitosan / Zn 2+ Curcumin-arginine mixed solution;
[0077] (4) System 1: Sodium hyaluronate / Zn 2+ The mixed solution of curcumin and arginine was poured into a six-well plate mold and freeze-dried to obtain sodium hyaluronate-curcumin / arginine-Zn 2+ Freeze-dried membrane (eg Figure 1 c);
[0078] System 2: Sodium hyaluronate / sulfonated chitosan / Zn 2+-The curcumin / arginine mixed solution was poured into a six-well plate mold and freeze-dried to obtain sodium hyaluronate / sulfonated chitosan-curcumin / arginine-Zn 2+ Freeze-dried membrane (eg Figure 2 c).
[0079] Example 2
[0080] (1) System 1: Take 0.05 g of sodium hyaluronate, dissolve it in 10 mL of deionized water, and stir it magnetically at room temperature for 12 h to obtain a sodium hyaluronate solution;
[0081] System 2: Take 0.1 g of sodium hyaluronate, dissolve it in 10 mL of deionized water, and stir it magnetically at room temperature for 12 h to obtain a sodium hyaluronate solution; take 0.1 g of sulfonated chitosan, dissolve it in 10 mL of deionized water, and stir it magnetically at room temperature for 2 h to obtain a sulfonated chitosan solution;
[0082] (2) System 1: Take 0.1725 mg Zn 2+ , add to the sodium hyaluronate solution in (1), stir evenly, and obtain sodium hyaluronate / Zn 2+ Solution;
[0083] System 2: Take 0.1725 mg Zn 2+ , add it to the sulfonated chitosan solution in (1), stir evenly, and obtain sulfonated chitosan / Zn 2+ Solution;
[0084] (3) Take the sodium hyaluronate / Zn obtained in (2) 2+ The solution and Cur / Arg solution were added into the mold at a mass ratio of 1:0.2 and stirred evenly to obtain sodium hyaluronate / Zn 2+ Curcumin / arginine mixed solution; take the sodium hyaluronate / Zn obtained in (2) 2+ Solution and sulfonated chitosan / Zn 2+ The solution was added into the mold at a ratio of 1:0.75 and stirred evenly to obtain sodium hyaluronate / Zn 2+ and sulfonated chitosan / Zn 2+ The mixed solution was then added with Cur / Arg solution at a mass ratio of 1:0.4 and stirred evenly to obtain sodium hyaluronate / sulfonated chitosan / Zn 2+ Curcumin / arginine mixed solution;
[0085] (4) System 1: Sodium hyaluronate / Zn 2+ The mixed solution of curcumin and arginine was poured into a six-well plate mold and freeze-dried to obtain sodium hyaluronate-curcumin / arginine-Zn 2+ Freeze-dried membrane;
[0086] System 2: Sodium hyaluronate / sulfonated chitosan / Zn2+ The curcumin / arginine mixed solution was poured into a six-well plate mold and freeze-dried to obtain sodium hyaluronate / sulfonated chitosan-curcumin / arginine-Zn 2+ .
[0087] Example 3
[0088] (1) System 1: Take 0.15 g of sodium hyaluronate, dissolve it in 10 mL of deionized water, and stir it magnetically at room temperature for 12 h to obtain a sodium hyaluronate solution;
[0089] System 2: Take 0.1 g of sodium hyaluronate, dissolve it in 10 mL of deionized water, and stir it magnetically at room temperature for 12 h to obtain a sodium hyaluronate solution; take 0.1 g of sulfonated chitosan, dissolve it in 10 mL of deionized water, and stir it magnetically at room temperature for 2 h to obtain a sulfonated chitosan solution;
[0090] (2) System 1: Take 0.1725 mg Zn 2+ , add to the sodium hyaluronate solution in (1), stir evenly, and obtain sodium hyaluronate / Zn 2+ Solution;
[0091] System 2: Take 0.1725 mg Zn 2+ , add it to the sulfonated chitosan solution in (1), stir evenly, and obtain sulfonated chitosan / Zn 2+ Solution;
[0092] (3) Take the sodium hyaluronate / Zn obtained in (2) 2+ The solution and Cur / Arg solution were added into the mold at a mass ratio of 1:0.6 and stirred evenly to obtain sodium hyaluronate / Zn 2+ Curcumin / arginine mixed solution; take the sodium hyaluronate / Zn obtained in (2) 2+ Solution and sulfonated chitosan / Zn 2+ The solution was added into the mold at a ratio of 0.8:1 and stirred evenly to obtain sodium hyaluronate / Zn 2+ and sulfonated chitosan / Zn 2+ The mixed solution was then added with Cur / Arg solution at a mass ratio of 1:0.4 and stirred evenly to obtain sodium hyaluronate sulfonated chitosan / Zn 2+ Curcumin / arginine mixed solution;
[0093] (4) System 1: Sodium hyaluronate / Zn 2+ The curcumin / arginine mixed solution was poured into a six-well plate mold and freeze-dried to obtain sodium hyaluronate / curcumin / arginine Zn 2+ Freeze-dried membrane;
[0094] System 2: Sodium hyaluronate / sulfonated chitosan / Zn 2+The curcumin / arginine mixed solution was poured into a six-well plate mold and freeze-dried to obtain sodium hyaluronate / sulfonated chitosan / curcumin / arginine Zn 2+ Lyophilize the membrane.
[0095] Example 4
[0096] (1) System 1: Take 0.1 g of sodium hyaluronate, dissolve it in 10 mL of deionized water, and stir it magnetically at room temperature for 12 h to obtain a sodium hyaluronate solution; System 2: Take 0.1 g of sodium hyaluronate, dissolve it in 10 mL of deionized water, and stir it magnetically at room temperature for 12 h to obtain a sodium hyaluronate solution; take 0.1 g of sulfonated chitosan, dissolve it in 10 mL of deionized water, and stir it magnetically at room temperature for 2 h to obtain a sulfonated chitosan solution;
[0097] (2) System 1: Take 0.1725 mg Zn 2+ , add to the sodium hyaluronate solution in (1), stir evenly, and obtain sodium hyaluronate / Zn 2+ Solution; System 2: Take 0.1725 mg Zn 2+ , add it to the sulfonated chitosan solution in (1), stir evenly, and obtain sulfonated chitosan / Zn 2+ Solution;
[0098] (3) Take the sodium hyaluronate / Zn obtained in (2) 2+ The solution and Cur / Arg solution were added into the mold at a mass ratio of 1:0.8 and stirred evenly to obtain sodium hyaluronate / Zn 2+ Curcumin arginine mixed solution; take the sodium hyaluronate / Zn obtained in (2) 2+ Solution and sulfonated chitosan / Zn 2+ The solution was added into the mold at a ratio of 0.6:1 and stirred evenly to obtain sodium hyaluronate / Zn 2+ and sulfonated chitosan / Zn 2+ The mixed solution was then added with Cur / Arg solution at a mass ratio of 1:0.4 and stirred evenly to obtain sodium hyaluronate / sulfonated chitosan / Zn 2+ Curcumin / arginine mixed solution;
[0099] (4) System 1: Sodium hyaluronate / Zn 2+ The mixed solution of curcumin and arginine was poured into a six-well plate mold and freeze-dried to obtain sodium hyaluronate / curcumin / arginine Zn 2+ Freeze-dried film; System 2: Sodium hyaluronate / sulfonated chitosan / Zn 2+ The curcumin / arginine mixed solution was poured into a six-well plate mold and freeze-dried to obtain sodium hyaluronate / sulfonated chitosan / curcumin / arginine Zn 2+ Lyophilize the membrane.
[0100] Experimental Example 1 Infrared spectroscopy (FT-IR) characterization
[0101] System 1: Take dried sodium hyaluronate, curcumin, arginine, zinc sulfate, curcumin / arginine, the physical mixture of the four, and the polysaccharide-based polymer material obtained in Example 1 and add them to dry KBr in a certain proportion, grind and mix them thoroughly, and place the mixture in a FTIR-8400S Fourier transform infrared spectrometer at 2 cm -1 The resolution is between 500 and 4000 cm -1 The IR spectra of sodium hyaluronate, curcumin, arginine, zinc sulfate, sodium hyaluronate / sulfonated chitosan, curcumin / arginine, a physical mixture of the four, and the polysaccharide-based polymer material prepared by system 1 in Example 1 were measured. The test results are shown in FIG. Figure 4 As shown by Figure 4 It can be seen that the polysaccharide-based polymer material does not show the absorption peak unique to the raw materials, indicating that sodium hyaluronate, curcumin, arginine and zinc sulfate have been successfully cross-linked to obtain a new type of polysaccharide-based medical polymer material.
[0102] System 2: Take dried sodium hyaluronate, chitosan, sulfonated chitosan, curcumin, arginine, curcumin / arginine, zinc sulfate, and the physical mixture of HA, SCS, Cur, Arg and ZnSO4·7H2O and the polysaccharide-based polymer material obtained in Example 1 and add them to dry KBr in a certain proportion, grind and mix them thoroughly, and place the mixture in a FTIR-8400S Fourier transform infrared spectrometer at 2 cm -1 The resolution is between 500 and 4000 cm -1 The IR spectra of sodium hyaluronate, chitosan, sulfonated chitosan, curcumin, arginine, curcumin / arginine, zinc sulfate, and the physical mixture of HA, SCS, Cur, Arg and ZnSO4·7H2O and the polysaccharide-based polymer material prepared by the system 2 of Example 1 were measured. The test results are shown in FIG. Figure 5 As shown by Figure 5 It can be seen that the polysaccharide-based polymer material does not show the absorption peak unique to the raw materials, indicating that sodium hyaluronate, sulfonated chitosan, curcumin, arginine, and zinc sulfate have been successfully cross-linked to obtain a new type of polysaccharide-based medical polymer material.
[0103] Experimental Example 2 Differential Scanning Calorimetry (DSC) Detection
[0104] System 1: Take appropriate amounts of sodium hyaluronate, curcumin, arginine, zinc sulfate, the physical mixture of the four, and the polysaccharide-based polymer material prepared by system 1 of Example 1, and perform DSC detection, scanning at 30°C~400°C. Determine the DSC spectrum of the physical mixture of sodium hyaluronate, curcumin, arginine, zinc sulfate, and the polysaccharide-based polymer material obtained in Example 1. The test results are as follows Figure 6 As shown by Figure 6 It can be seen that the polysaccharide-based polymer material does not show the absorption peak unique to the raw materials, indicating that sodium hyaluronate, curcumin, arginine and zinc sulfate have been successfully chelated to obtain a new type of polysaccharide-based medical polymer material.
[0105] System 2: Take appropriate amounts of sodium hyaluronate, sulfonated chitosan, sodium hyaluronate / sulfonated chitosan, curcumin, arginine, zinc sulfate, and the physical mixed samples of the six and the polysaccharide-based polymer material prepared by system 2 of Example 2, and perform DSC detection, scanning at 30°C~400°C. Determine the DSC spectrum of the physical mixed samples of sodium hyaluronate, sulfonated chitosan, sodium hyaluronate / sulfonated chitosan, curcumin, arginine, zinc sulfate, and the polysaccharide-based polymer material obtained in Example 2. The test results are as follows Figure 7 As shown by Figure 7 It can be seen that the polysaccharide-based polymer material does not show the absorption peak unique to the raw materials, indicating that sodium hyaluronate, sulfonated chitosan, curcumin, arginine, and zinc sulfate have been successfully chelated to obtain a new type of polysaccharide-based medical polymer material.
[0106] Test Example 3 Water Vapor Transmission Rate (WVTR) Test
[0107] System 1: Take the sodium hyaluronate-curcumin / arginine-Zn prepared in Example 1 2+ The freeze-dried membrane was placed in a desiccator to dry, and the dried membrane sample was fixed on the opening of a bottle containing 10 mL of deionized water, and sealed completely to ensure that no water vapor escaped from the bottle mouth except for the membrane dressing. All experimental components were carried out in a biochemical incubator at 37 ° C and a relative humidity of 35%, with the evaporation of water vapor as a control. After 24 hours, the sample was taken out and weighed. Three parallel experiments were performed and the average value was calculated. The initial weight of the bottle + 10 mL of water + membrane was recorded as W0, and after 24 hours, the weight of the bottle + water + membrane was recorded as W t, WVTR (g·m -2 ·d -1 )=(W0-W t ) / S,
[0108] Where W0 represents the weight of the initial bottle + 10 mL of water + membrane, W t represents the weight of bottle + water + film, S represents the area of the bottle mouth (m 2). The results of the water vapor transmission rate test are shown in Figure 8 ,Depend on Figure 8 It can be seen that sodium hyaluronate-curcumin / arginine-Zn 2+ The freeze-dried film has a good water vapor permeability, indicating that the prepared sodium hyaluronate polysaccharide polymer material has a significant ability to absorb wound exudate.
[0109] System 2: Sodium hyaluronate / sulfonated chitosan-curcumin / arginine-Zn prepared in Example 2 2+ The freeze-dried membrane was placed in a desiccator to dry, and the dried membrane sample was fixed on the opening of a bottle containing 10 mL of deionized water, and sealed completely to ensure that no water vapor escaped from the bottle mouth except for the membrane dressing. All experimental components were carried out in a biochemical incubator at 37 ° C and a relative humidity of 35%, with the evaporation of water vapor as a control. After 24 hours, the sample was taken out and weighed. Three parallel experiments were performed and the average value was calculated. The initial weight of the bottle + 10 mL of water + membrane was recorded as W0, and after 24 hours, the weight of the bottle + water + membrane was recorded as W t, WVTR (g·m -2 ·d -1 )=(W0-W t ) / S,
[0110] Where W0 represents the weight of the initial bottle + 10 mL of water + membrane, W t represents the weight of bottle + water + film, S represents the area of the bottle mouth (m 2 ). The results of the water vapor transmission rate test are shown in Fig. 9 ,Depend on Fig. 9 It can be seen that sodium hyaluronate / sulfonated chitosan-curcumin / arginine-Zn 2+ (HA / SCS-Cur / Arg-Zn 2+ ) The freeze-dried film has a good water vapor permeability, indicating that the prepared HA / SCS-Cur / Arg-Zn 2+ The material has a significant ability to absorb wound exudate.
[0111] It can be seen that sulfonated chitosan has good antibacterial, anti-inflammatory, antioxidant and angiogenesis-promoting effects. Therefore, from the perspective of wound repair efficacy, sodium hyaluronate / sulfonated chitosan-curcumin / arginine-Zn 2+ The membrane material has better efficacy than the membrane material in Example 1. The experimental results have actually proved that the addition of SCS can promote wound healing, and the effect is better than that of sodium hyaluronate-curcumin / arginine-Zn 2+ Freeze-dried membrane is better.
[0112] Test Example 4 In vitro antioxidant test
[0113] System 1: Take the hyaluronic acid polysaccharide polymer material prepared in Example 1, and use deionized water to prepare solutions with mass concentrations of hyaluronic acid polysaccharide polymer material of 0.625 mg / mL, 1.25 mg / mL, 2.5 mg / mL, 5 mg / mL, and 10 mg / mL, respectively, and shake until all dissolved;
[0114] Sodium hyaluronate, sodium hyaluronate-curcumin / arginine, and sodium hyaluronate-curcumin / arginine-zinc ion were prepared with deionized water into solutions with mass concentrations of 0.625 mg / mL, 1.25 mg / mL, 2.5 mg / mL, 5 mg / mL, and 10 mg / mL, respectively;
[0115] Take 100 μL of the above-mentioned sodium hyaluronate, sodium hyaluronate-curcumin / arginine, sodium hyaluronate-curcumin / arginine-zinc ion solutions of different concentrations, incubate with 100 μL of DPPH solution with a mass concentration of 0.01 mg / mL in the dark for 30 minutes, measure the absorbance at a wavelength of 517 nm, and perform three parallel tests.
[0116] The DPPH free radical scavenging rate of the above substances at different concentrations was calculated by the following formula: DPPH inhibition % = (1-(A 样品 -A 空白 )÷A 对照 )×100%,
[0117] Where A 样品 is the absorbance of the sample and DPPH, A 空白 is the absorbance of the sample and anhydrous ethanol, A 对照 is the absorbance of deionized water and DPPH. Fig.10 As shown by Fig.10 It can be seen that hyaluronic acid polysaccharide polymer material has certain free radical scavenging properties.
[0118] System 2: Take the hyaluronic acid polysaccharide polymer material prepared in Example 2, and use deionized water to prepare solutions with mass concentrations of hyaluronic acid sulfonated chitosan polysaccharide polymer material of 0.625 mg / mL, 1.25 mg / mL, 2.5 mg / mL, 5 mg / mL, and 10 mg / mL, respectively, and shake until all dissolved;
[0119] Sodium hyaluronate, sulfonated chitosan, sodium hyaluronate / sulfonated chitosan, sodium hyaluronate / sulfonated chitosan-curcumin / arginine, sodium hyaluronate / sulfonated chitosan-curcumin / arginine-zinc ion were prepared with deionized water to prepare solutions with mass concentrations of 0.625 mg / mL, 1.25 mg / mL, 2.5 mg / mL, 5 mg / mL, and 10 mg / mL, respectively;
[0120] Take 100 μL of the above-mentioned solutions of different concentrations of sodium hyaluronate, sulfonated chitosan, sodium hyaluronate / sulfonated chitosan, sodium hyaluronate / sulfonated chitosan-curcumin / arginine, sodium hyaluronate / sulfonated chitosan-curcumin / arginine-zinc ion, incubate with 100 μL of DPPH solution with a mass concentration of 0.01 mg / mL in the dark for 30 min, measure the absorbance at a wavelength of 517 nm, and detect three times in parallel.
[0121] The DPPH free radical scavenging rate of the above substances at different concentrations was calculated by the following formula: DPPH inhibition % = (1-(A 样品 -A 空白 )÷A 对照 )×100%,
[0122] Where A 样品 is the absorbance of the sample and DPPH, A 空白 is the absorbance of the sample and anhydrous ethanol, A 对照 is the absorbance of deionized water and DPPH. Fig.11 As shown by Fig.11 It can be seen that hyaluronic acid polysaccharide polymer material has certain free radical scavenging properties.
[0123] Test Example 5 In vitro antibacterial test
[0124] System 1: Preparation of solid culture medium: LB solid culture medium;
[0125] Preparation of Staphylococcus aureus suspension: LB liquid medium;
[0126] The concentration is 1.0×10 8 100 μL of Staphylococcus aureus suspension with CFU / mL was placed on the solid culture medium and spread evenly with a sterile cotton swab;
[0127] The sterile filter paper was punched into a filter paper disc with a diameter of 8 mm using a hole puncher, and the sterile filter paper disc with a diameter of 8 mm, sodium hyaluronate, sodium hyaluronate-curcumin / arginine, and sodium hyaluronate-curcumin / arginine-zinc ion were placed on the solid culture medium coated with the Staphylococcus aureus suspension, and marked with a signature pen, and cultured at 37°C for 24 hours, and the results were observed and recorded. The process was repeated three times in parallel.
[0128] The in vitro antibacterial test of Escherichia coli was carried out in the same manner as above.
[0129] The test results are as follows Fig.12 As shown by Fig.12 It can be seen that hyaluronic acid polysaccharide polymer material has certain antibacterial properties against Staphylococcus aureus and Escherichia coli.
[0130] System 2: Preparation of solid culture medium: LB solid culture medium;
[0131] Preparation of Staphylococcus aureus suspension: LB liquid medium;
[0132] The concentration is 1.0×10 8 100 μL of Staphylococcus aureus suspension with CFU / mL was placed on the solid culture medium and spread evenly with a sterile cotton swab;
[0133] The sterile filter paper was punched into a filter paper disc with a diameter of 8 mm using a hole puncher, and the sterile filter paper disc with a diameter of 8 mm, sodium hyaluronate, chitosan, sulfonated chitosan, sodium hyaluronate / sulfonated chitosan, sodium hyaluronate / sulfonated chitosan-curcumin / arginine, sodium hyaluronate / sulfonated chitosan-curcumin / arginine-zinc ion were placed on the solid culture medium coated with the Staphylococcus aureus suspension, marked with a signature pen, cultured at 37°C for 24 hours, and the results were observed and recorded. The process was repeated three times in parallel.
[0134] The in vitro antibacterial test of Escherichia coli was carried out in the same manner as above.
[0135] The test results are as follows Fig.13 As shown by Fig.13 It can be seen that the hyaluronic acid sulfonated chitosan polysaccharide polymer material has certain antibacterial properties against Staphylococcus aureus and Escherichia coli.
[0136] Test Example 6 In vitro hemolytic test
[0137] System 1: Take 1 mL of fresh blood from Wistar rats and add appropriate amount of heparin to make anticoagulated whole blood;
[0138] Take the above anticoagulated whole blood, dilute it with sterile PBS buffer at a volume ratio of 1:4, mix it, centrifuge it at 2500 rpm / min for 15 min to obtain red blood cells, add 9 mL of sterile PBS, and mix it evenly to form a red blood cell suspension;
[0139] 1 mg of the hyaluronic acid polysaccharide polymer material obtained in Example 1 was mixed evenly with 1 mL of the above red blood cell suspension to serve as the experimental group sample;
[0140] Take the above red blood cells and mix them with sterile deionized water at a volume ratio of 1:9 as a positive control sample;
[0141] The above red blood cell suspension was used as the negative control sample. 1 mL of each of the negative control sample, positive control sample and experimental group sample were incubated together at 37°C for 1 h, centrifuged at 2500 rpm for 15 min, and the supernatant was taken respectively, and the absorbance was measured at a wavelength of 540 nm; the negative control sample, positive control sample and experimental group sample were each repeated three times.
[0142] The above-mentioned hemolytic test was performed on sodium hyaluronate, sodium hyaluronate-curcumin / arginine, and sodium hyaluronate-curcumin / arginine-zinc ion in the same manner.
[0143] The hemolysis rate was calculated according to the following formula: Hemolysis Rate(%)=((ABS experiment -ABS negative ) / (ABS positive -ABS negative ))×100%,
[0144] Among them, ABS experiment is the absorbance of the sample solution, ABS negative is the absorbance of the negative control, ABS positive is the absorbance of the positive control. Fig.14 As shown by Fig.14 It can be seen that the hemolysis rates of sodium hyaluronate, sodium hyaluronate-curcumin / arginine, and sodium hyaluronate-curcumin / arginine-zinc ion are all less than 2%, which meets the requirement of the medical material standard that the hemolysis rate is less than 5%. Therefore, the hyaluronic acid polysaccharide polymer material will not have hemolysis.
[0145] System 2: Take 1 mL of fresh blood from Wistar rats and add appropriate amount of heparin to make anticoagulated whole blood;
[0146] Take the above anticoagulated whole blood, dilute it with sterile PBS buffer at a volume ratio of 1:4, mix it, centrifuge it at 2500 rpm / min for 15 min to obtain red blood cells, add 9 mL of sterile PBS, and mix it evenly to form a red blood cell suspension;
[0147] 1 mg of the hyaluronic acid polysaccharide polymer material obtained in Example 1 was mixed evenly with 1 mL of the above red blood cell suspension to serve as the experimental group sample;
[0148] Take the above red blood cells and mix them with sterile deionized water at a volume ratio of 1:9 as a positive control sample;
[0149] The above red blood cell suspension was used as the negative control sample. 1 mL of each of the negative control sample, positive control sample and experimental group sample were incubated together at 37°C for 1 h, centrifuged at 2500 rpm for 15 min, and the supernatant was taken respectively, and the absorbance was measured at a wavelength of 540 nm; the negative control sample, positive control sample and experimental group sample were each repeated three times.
[0150] The above-mentioned hemolytic test was performed on sodium hyaluronate, sulfonated chitosan, sodium hyaluronate / sulfonated chitosan, sodium hyaluronate / sulfonated chitosan-curcumin / arginine, and sodium hyaluronate / sulfonated chitosan-curcumin / arginine-zinc ion in the same manner.
[0151] The hemolysis rate was calculated according to the following formula: Hemolysis Rate(%)=((ABS experiment -ABS negative ) / (ABS positive -ABS negative ))×100%,
[0152] Among them, ABS experiment is the absorbance of the sample solution, ABS negative is the absorbance of the negative control, ABS positive is the absorbance of the positive control. Fig.15 As shown by Fig.15 It can be seen that the hemolysis rates of sodium hyaluronate, sulfonated chitosan, sodium hyaluronate / sulfonated chitosan, sodium hyaluronate / sulfonated chitosan-curcumin / arginine, sodium hyaluronate / sulfonated chitosan-curcumin / arginine-zinc ion are all less than 2%, which meets the requirement of the medical material standard that the hemolysis rate is less than 5%. Therefore, the hyaluronic acid polysaccharide polymer material will not have hemolysis.
[0153] Test Example 7 Diabetes Wound Healing Test
[0154] Wistar rats weighing about 200 g were fasted for 12 h, weighed, and the dosage was calculated. The fasting blood glucose level was measured. The intraperitoneal injection of alloxan was 120 mg / kg. The second administration was 24 h later, and the intraperitoneal injection of alloxan was 100 mg / kg. After the first intraperitoneal injection of alloxan, the drinking water was replaced with 20% glucose solution, and the high-sugar drinking water was maintained for 1 week. At the end of 7 days, rats with fasting random blood glucose levels greater than 16.7 mmol / L were selected as type II diabetic rats. During the experiment, the fasting blood glucose levels of the experimental rats were monitored to verify the stability of the diabetic animal model. After monitoring the blood glucose value at the end of 7 days, the model was successfully established if the blood glucose value was greater than 16.7 mmol / L.
[0155] System 1: Successfully modeled Wistar rats were randomly divided into a diabetic blank group, a 3Tegaderm dressing group, a normal group, HA, HA-Cur / Arg, and HA-Cur / Arg-Zn 2+ , 3 rats in each group, the backs of the rats were shaved, and a full-thickness circular wound (1.5 cm × 1.5 cm) was created with scissors;
[0156] The diabetic blank group and the normal group were directly bandaged with gauze without any dressing or medicine; the 3Tegaderm dressing was used to bandage the wound with a commercially available 3M dressing; the other groups were bandaged with a 2.4×2.4 cm membrane material prepared in Example 1 and gauze; the wound healing of the diabetic rats was observed after 19 days. The results are as follows: Fig.16 As shown. Fig.16 It can be seen that hyaluronic acid polysaccharide polymer materials can significantly promote diabetic wound healing.
[0157] System 2: Wistar rats with successful modeling were randomly divided into diabetic blank group, 3Tegaderm dressing group, normal group, HA group, SCS group, HA / SCS group, HA / SCS-Cur / Arg group, HA / SCS-Cur / Arg-Zn group, and HA / SCS-Cur / Arg-Zn group. 2+ Group, 3 rats in each group, the back of the rats was shaved, and a full-thickness circular wound (1.5 cm × 1.5 cm) was created with scissors;
[0158] The diabetic blank group and the normal group were directly bandaged with gauze without any dressing or medicine; the 3Tegaderm dressing was used to bandage the wound with a commercially available 3M dressing; the other groups were bandaged with a 2.4×2.4 cm membrane material prepared in Example 2 and gauze; the wound healing of the diabetic rats was observed after 19 days. The results are as follows: Fig.17 As shown. Fig.17 It can be seen that hyaluronic acid sulfonated chitosan polysaccharide polymer material can significantly promote diabetic wound healing.
[0159] The above is only a specific implementation of the present disclosure, but the protection scope of the present disclosure is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present disclosure should be included in the protection scope of the present disclosure. Therefore, the protection scope of the present disclosure should be based on the protection scope of the claims.
Claims
1. A method for preparing a wound repair membrane, characterized in that: The preparation method comprises: Step (1): Dissolve sodium hyaluronate in deionized water and add appropriate amount of Zn 2+ , stir evenly to obtain sodium hyaluronate / Zn 2+ Solution; Step (2): dissolving curcumin in arginine, and uniformly stirring at a set temperature to obtain a curcumin / arginine solution; Step (3): The sodium hyaluronate / Zn obtained in step (1) 2+ The solution is added to the curcumin / arginine solution obtained in step (2), and stirred evenly to obtain a sodium hyaluronate-curcumin-arginine-zinc ion mixed solution; Step (4): introducing the sodium hyaluronate-curcumin-arginine-zinc ion mixed solution obtained in step (3) into a repair film preparation mold, and freeze-drying under set conditions to obtain a sodium hyaluronate-curcumin-arginine-zinc ion freeze-dried film.
2. The method for preparing the wound repair membrane according to claim 1, characterized in that: The preparation method further comprises: Step (5): Dissolve sulfonated chitosan in deionized water and add a certain amount of Zn 2+ , stir evenly to obtain sulfonated chitosan / Zn 2+ Solution; The step (3) comprises: mixing the sodium hyaluronate / Zn obtained in step (1) 2+ Solution and the sulfonated chitosan / Zn obtained in step (5) 2+ The solution was mixed according to the set ratio, added to the curcumin / arginine solution, and stirred evenly to obtain sodium hyaluronate / sulfonated chitosan-curcumin / arginine-Zn 2+ Mixing solutions; Step (4) comprises: introducing the sodium hyaluronate-curcumin-arginine-zinc ion mixed solution obtained in step (3) into a repair film preparation mold, and freeze-drying under set conditions to obtain sodium hyaluronate / sulfonated chitosan-curcumin / arginine-Zn 2+ Lyophilize the membrane.
3. The method for preparing the wound repair membrane according to claim 1, characterized in that: The mass ratio of sodium hyaluronate to sulfonated chitosan in step (3) is 1:0.
5.
4. The method for preparing the wound repair membrane according to claim 1, characterized in that: The sodium hyaluronate / Zn in step (3) 2+ Solution and sulfonated chitosan / Zn 2+ The mass ratio of the mixed solution to curcumin / arginine was 1:0.
4.
5. The method for preparing the wound repair membrane according to any one of claims 1 to 4, characterized in that: The mass ratio of curcumin to arginine in step (2) is 1:18; the set temperature in step (2) is 60-80°C.
6. The method for preparing the wound repair membrane according to any one of claims 1 to 4, characterized in that: The mass concentration of sodium hyaluronate in step (1) is 10 mg / mL, and Zn is added 2+ The concentration is 60 μmol / L.
7. The method for preparing the wound repair membrane according to any one of claims 1 to 4, characterized in that: The freeze drying conditions under the set conditions in step (4) are: the freeze drying temperature is -60~-70°C, the freeze drying vacuum is 1~5Pa, and the freeze drying time is 20~24h.
8. A wound repair membrane, characterized in that: The wound repair membrane is prepared by the preparation method of the wound repair membrane according to any one of claims 1 to 7.
9. A wound repair dressing used for wound healing, characterized in that: The wound repair dressing comprises the wound repair film as described in claim 8.
Citation Information
Patent Citations
Curcumin-loaded hydrogel for repairing chronic wound surface of diabetes and preparation method of curcumin-loaded hydrogel
CN115068684A
Alginic acid polysaccharide polymer gel film agent as well as preparation method and application thereof
CN115671362A
Collagen sponge dressing and preparation method thereof
CN116077707A
Hydrogel dressing with self-repairing and injectable functions as well as preparation method and application of hydrogel dressing
CN118252970A